2010
DOI: 10.1111/j.1365-2842.2010.02085.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of jerk-cost using a triaxial piezoelectric accelerometer for the evaluation of jaw movement smoothness

Abstract: Jerk-cost as a measure of jaw movement smoothness has been used to evaluate the masticatory function of patients with tooth loss and malocclusion. Jerk-cost measuring systems have thus far been unable to determine the jerk-cost of each chewing phase over time. The purposes of this study were (i) to develop a new method for measuring momentary jerk-cost of the jaw movement using a small triaxial piezoelectric accelerometer and (ii) to test the hypothesis that the lowest smoothness is seen during jaw-opening pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 22 publications
2
32
1
Order By: Relevance
“…Each recording was performed over only one session to avoid changes in the subject’s skilfulness of chewing through repetition of the task too many times. The reliability of this procedure was confirmed in a previous study (23).…”
Section: Methodssupporting
confidence: 73%
See 2 more Smart Citations
“…Each recording was performed over only one session to avoid changes in the subject’s skilfulness of chewing through repetition of the task too many times. The reliability of this procedure was confirmed in a previous study (23).…”
Section: Methodssupporting
confidence: 73%
“…Exclusion criteria were as follows: history of temporomandibular muscle and joint disorders (TMJD) and severe periodontal disease, dental caries. Some of the procedures have been previously described (4, 23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the jaw‐opening phase in gum chewing is associated with minimum smoothness because of the adhesive nature or viscosity of gum and the cycle‐by‐cycle modifications of the jaw, tongue, and lip movements during jaw opening . The observation that jerk‐cost was higher during the opening B phase and the closing A phase of gum chewing than during empty chewing suggests that the influence of the mechanical effects of tooth contact on jerk‐cost is not restricted just to the occlusal phase of chewing, but rather the effect influences the entire opening and closing phases of chewing.…”
Section: Discussionmentioning
confidence: 99%
“…These forces may be static, like the constant force of gravity, or they could be dynamic caused by moving or vibrating the accelerometer. They are undesirable for detecting mandibular movement as they do not produce stable recordings of the static position of the mandible [6,7,8].…”
Section: Introductionmentioning
confidence: 99%